2018
DOI: 10.1101/426668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational design of hidden thermodynamic driving through DNA mismatch repair

Abstract: Recent years have seen great advances in the development of synthetic self-assembling molecular systems. Designing out-of-equilibrium architectures, however, requires a more subtle control over the thermodynamics and kinetics of reactions. We propose a new mechanism for enhancing thermodynamic drive of DNA strand displacement reactions whilst barely perturbing forward reaction rates -introducing mismatches in an internal location within the initial duplex. Through a combination of experiment and simulation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The observed slowdown induced by mismatches at different positions for RNA TMSD is hence compatible with the kinetics of TMSD of DNA strands with mismatches that was previously studied computationally and experimentally [26,27,34]. The kinetics of the TMSD can be approximately modeled as a stochastic Markovian process consisting of transitions between states characterized by the number of bonds between respective strands.…”
Section: B Mismatch Effectssupporting
confidence: 82%
See 3 more Smart Citations
“…The observed slowdown induced by mismatches at different positions for RNA TMSD is hence compatible with the kinetics of TMSD of DNA strands with mismatches that was previously studied computationally and experimentally [26,27,34]. The kinetics of the TMSD can be approximately modeled as a stochastic Markovian process consisting of transitions between states characterized by the number of bonds between respective strands.…”
Section: B Mismatch Effectssupporting
confidence: 82%
“…Furthermore, the effects of mismatches between the invader and the substrate on the displacement kinetics of DNA TMSD has been studied in Ref. [26,27]. In the case of "mismatch repair" the mismatches were placed between the incumbent and substrate and therefore corrected by the displacement [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A coarse-grained model of DNA was also used to study strand displacement reactions through simulation, providing a more structural and physical understanding of the underlying mechanism . Furthermore, investigations into the effects of mismatched base pairs between the invader and the substrate in DNA TMSD have demonstrated that the kinetics are highly dependent on the position of the mismatch. …”
Section: Introductionmentioning
confidence: 99%